(untitled) (CAHIERS MAGELLANES-NS, 2024)
To ensure efficient design of long-duration flights, it is important to address the common issues of high surface temperature and aerodynamic drag during high-speed flights. The numerical analysis conducted for this study utilized a free stream condition of Mach 8.0, which is expected to result in turbulent flow. The aim of this study is to investigate how active and passive cooling methods synergistically reduce drag in hypersonic flight, particularly using a short spike, through numerical simulations aimed at enhancing aerodynamic efficiency and thermal management. The numerical analysis was conducted using ANSYS Fluent on a model with a blunted cone, bluntness ratio of 0.86, cone base diameter 70 mm, and a sharp spike of different sizes located in the leading nose region. Unlike many existing studies that do not consider the turbulent model for incoming freestream flow, this investigation incorporated the k-ω turbulent model to capture turbulent phenomena. Based on the numerical results, the short spike device was found to reduce pressure drag on the forward heat shield by up to 23.78%. Utilizing a short spike in conjunction with a counter jet at a maximum pressure ratio of 43.7 resulted in a significant drag reduction of about 86.9%. This research presents an innovative technique for reducing drag in hypersonic flights through the combined use of active and passive cooling strategies. By integrating a short spike with a counter jet at a maximum pressure ratio of 43.7 that achieved a remarkable drag reduction of around 86.9%. The synergy between the passive spike and the active counter jet demonstrates significant potential for enhancing aerodynamics in high-speed flight conditions. These numerical findings suggest that the newly developed device has significant potential to serve as an effective protection heat shield for hypervelocity flight in the future.